Cognitive and motor outcomes of children with prenatal opioid exposure: a systematic review and meta-analysis - Yeoh, SL; Eastwood, J; Wright, IM; Morton, R; Melhuish, E; Ward, M; Oei, JL (JAMA Network, 2019)
Importance: Prenatal opioid exposure (POE) is one of the fastest-growing global health problems, but its association with long-term neurologic and physical development remains unknown.